Design of a Live-Line Inspection Robot System for Insulators in UHVDC Transmission Lines - Yan, Yunfeng; Sun, Hao; Hao, Fei; Chen, Peng; Zhang, Tianlong; Yang, Zehua (EAI Endorsed Transactions on Energy Web, 2026)
To address the pain points of low-zero insulators in UHVDC transmission lines, which are prone to insulation flashover, and the low accuracy, reliance on manual labor, and weak anti-interference capabilities of traditional inspection methods, this study developed an integrated live-line inspection robot that combines mechanical climbing, precise inspection, intelligent control, and electromagnetic shielding. The robot system comprises a mechanical system (tracked movement mechanism, guiding and clamping mechanism), detection system (2500V high-voltage detection circuit, MEGA128 microcontroller control), control system (L298N motor drive, frequency-hopping spread spectrum wireless data transmission), and electromagnetic shielding system (multi-layer shielding shell, opto-isolation, multi-point common ground). An innovative "equipotential bypass" detection principle is proposed to eliminate leakage current interference, and an improved PSO-SVR fusion algorithm is introduced to optimize the detection data. Experimental verification showed that in laboratory tests, the robot exhibited excellent electromagnetic interference resistance (shielding effectiveness SE≥ 60 dB) and a resistance measurement error ≤±2.5%. In actual live-line testing of 500 kV/1000 kV lines, the detection error was ≤±3%, the detection cycle for a single string (28/32 pieces) was only 92 108s, the detection rate of degraded insulators was 100%, and it eliminated the need for power outages and manual tower climbing. This robot meets the "live-line, accurate, efficient, and interference-resistant" detection requirements of UHV lines, providing reliable technical support for the intelligent operation and maintenance of power grids and has broad engineering application prospects.